STUDI PEMBELAJARAN DENGAN MENERAPKAN KETERAMPILAN PROSES DI BEBERAPA SEKOLAH DASAR WRINGINANOM-GRESIK - Mia Alifya Djuliyanti; Muhammad Thamrin Hidayat; Akhwani Akhwani; Nafiah Nafiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This study aimed to reveal the implementation of process skills in the learning process at several Elementary Schools in Wringinanom-Gresik. The method in this study was descriptive qualitative research. The data were collected through a closed questionnaire using a Likert scale with 4 choices, namely SA (Strongly Agree), A (Agree), D (Disagree), SD (Strongly Disagree). The respondents in this study were 21 teachers from several elementary schools. Based on the results obtained fromt the respondents, it was found that 81% of the teachers agreed and applied the process skills while 18% of the respondents disagreed. This was because not all learning models were applicable by using process skills. This study concluded that the majority of teachers at Elementary Schools in Wringinanom - Gresik implemented and agreed the learning process with process skills. In addition, it was also found that the teachers' knowledge about the process skills was good.